2004
DOI: 10.1046/j.1600-6143.2003.00297.x
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from Pure Red Cell Aplasia Caused by Anti Erythropoietin Antibodies After Kidney Transplantation

Abstract: The use of recombinant human erythropoietin (rHuEPO) is a major advance in the treatment of patients with anemia caused by chronic renal failure (CRF). The development of antierythropoietin (anti-EPO) antibodies following treatment with rHuEPO has been observed in an increasing number of patients. This causes pure red cell aplasia (PRCA) and requires the definitive withdrawal of rHuEPO. Many patients require immunosuppressive therapy before anti-EPO antibodies disappear completely. We report a case of PRCA owi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
(15 reference statements)
0
9
0
Order By: Relevance
“…A more recent study concurred with these findings, showing an increased EPO concentration (in the absence of exogenous administration) in anemic patients compared with nonanemic patients after transplantation (20). It is interesting that it has been documented that anti-EPO antibodies that occasionally are responsible for severe anemia before transplantation tend to disappear after initiation of immunosuppression at the time of transplantation (21).…”
Section: Causes and Correlatesmentioning
confidence: 68%
“…A more recent study concurred with these findings, showing an increased EPO concentration (in the absence of exogenous administration) in anemic patients compared with nonanemic patients after transplantation (20). It is interesting that it has been documented that anti-EPO antibodies that occasionally are responsible for severe anemia before transplantation tend to disappear after initiation of immunosuppression at the time of transplantation (21).…”
Section: Causes and Correlatesmentioning
confidence: 68%
“…17,18 Other studies have revealed that despite the new therapeutic and clinical approaches, the survival rate remains unsatisfactory. 19,20 The patient in the present report received a regimen of high doses of steroids (dexamethasone, 40 mg) in association with a proteosome inhibitor (bortezomib, 0.7 mg/m 2 ), and despite its toxicity, it led the patient to a good response with good tolerance, and an increase in the patient's quality of life. Because he presented stage V renal disease with hemodialysis support, age above 65 years and slightly increased basal brain natriuretic peptide, the patient did not fulfill the criteria for stem cell transplantation and was classified as high risk.…”
Section: Discussionmentioning
confidence: 84%
“…In a retrospective survey of 47 patients with erythropoietin‐induced PRCA, 37 received immunosuppressive therapy and 78% of these patients were cured of PRCA. Renal transplantation was associated with cure of PRCA in all of the reported patients (6, 12, 13). The course of the disease in our patient differs significantly from other reports in the literature.…”
Section: Discussionmentioning
confidence: 85%